Analysis of Feeder Train Travel Planning to Support Service (Whoosh) on The Bandung – Padalarang Line - Agus Nugroho; Prayudi Prayudi; Ahmad Fauzan Gunawan (Green Publisher, 2025)
Transportation makes the backbone of a country's economic and social development In Indonesia, improving transportation infrastructure is one of the priorities to support prolonged economic growth. One of the major breakthroughs in the field of transportation in Indonesia is the development of high speed trains (fast trains), which is expected to provide a solution to the mobility needs that are currently very high between big cities. In reality, the train does not route from the center of Jakarta and the center of Bandung City, so a supporting mode is needed, which in this case is the Bandung-Padalarang feeder train. In order to facilitate the process of designing the feeder train travel line/adwal, this study uses JtrainGraph software. This study also uses a quantitative descriptive method. The results of the analysis show that the current Bandung-Padalarang crossing capacity is sufficient to accommodate the increase in the frequency of feeder train trips. However, it is necessary to adjust the schedule and operation arrangements to ensure optimal connectivity between the feeder train and the high-speed train service (Whoosh), so that the journey/operation of the feeder train has been planned in the form of travel lines or schedules using the Jtraingraph software as mentioned above. This study provides input on the adjustment of feeder train schedules/trips and related trains that are important for the development of railway operations on the Bandung-Padalarang route to support better service integration.